Off-pore Nup98 condensates mobilize heterochromatic breaks and exclude Rad51 - Merigliano, Chiara; Ryu, Taehyun; Cibulka, Jakub; Rawal, Chetan C; See, Colby D; Mitra, Anik; Reynolds, Trevor W; Butova, Nadejda L; Caridi, Christopher P; Li, Xiao; Wang, Jeff; Deng, Changfeng; et al. (Molecular cell, 2025)
Phase separation forms membraneless compartments, including heterochromatin "domains" and repair foci. Pericentromeric heterochromatin mostly comprises repeated sequences prone to aberrant recombination. In Drosophila cells, "safe" homologous recombination (HR) repair of these sequences requires their relocalization to the nuclear periphery before Rad51 recruitment and strand invasion. How this mobilization initiates is unknown, and the contribution of phase separation is unclear. Here, we show that Nup98 nucleoporin is recruited to repair sites before relocalization by Sec13 or Nup88, and downstream of the Smc5/6 complex and heterochromatin protein 1 (HP1). Remarkably, Nup98 condensates are immiscible with HP1 condensates, and they are required and sufficient to mobilize repair sites and exclude Rad51, thus preventing aberrant recombination while promoting HR repair. Disrupting this pathway results in heterochromatin repair defects and widespread chromosome rearrangements, revealing an "off-pore" role for nucleoporins and phase separation in nuclear dynamics and genome integrity in a multicellular eukaryote.
Keywords: phase separation; Drosophila melanogaster; Chromosomal Proteins, Non-Histone; Drosophila Proteins; homolog proteinu s chromoboxem 5; proteiny Drosophily; heterochromatin repair; double-strand break repair; homologous recombination; heterochromatin; Recombinational DNA Repair; Nup88; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; rekombinační oprava DNA; Sec13; Rad51 Recombinase; rekombinasa Rad51; Nuclear Pore Complex Proteins; proteiny buněčného cyklu; Animals; Nup98 condensates; droplets; Heterochromatin; zvířata; Chromobox Protein Homolog 5; nuclear dynamics; chromozomální proteiny, nehistonové; Cell Cycle Proteins; nucleoplasmic nucleoporins; komplex proteinů jaderného póru